Design and Manufacture of Nanomedicine for Aflax Pump Inhibitors in Clinical Isolates of Methicillin-Resistant Staphylococcus Aureus (MRSA) Bacteria - Banafshe Sayadi Rad1 , Anoosh Eghdami21 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The consequences of this bacterium can be severe. Methicillin is one of these drugs, this drug, like other betalactams, inhibits Trans peptidases by binding to penicillin-binding protein (PBP). It prevents the formation ofpeptide glycans in the bacterial cell wall and destroys the bacterial cell wall. Chemical structure modificationhas made it resistant to the beta-lactamase enzyme produced by some bacteria. It was made in 1959. Today, ithas been removed from the list of drugs and better alternatives such as cloxacillin and nafsilin are available.It has a lower spectrum than penicillin but it works well against beta-lactamase-producing organismssuch as Staphylococcus aureus. Design and manufacture of nanoparticles for Aflax pump inhibitors inmethicillin-resistant Staphylococcus aureus bacteria Preparation of BSA-meticillin nano-drug: This wasdone using the desolvation method and after ensuring the formation of nanodars using the XRD and FT-IRspectra, Microdiagnostic antibiogram testing was performed on methicillin-resistant Staphylococcus aureusand the phenotypic pump activity of all isolates was performed by agar technique containing Ethidiumbromide by vil card method. According to a study, the Nano medicine albumin-methicillin has the highestinhibition of methylcellulose-resistant Staphylococcus aureus Aflax pump.